The Diversity and Distribution of Sponges in Three Different Islands at the Makassar Strait, Indonesia - Sukri, Nurul Magfirah; Priawandiputra, Windra; Atmowidi, Tri; Litaay, Magdalena (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Approximately 3978 sponge individuals were collected and grouped to 137 morphospecies, with 120 of these have been identified intothree classes, 17 orders, 40 families, and at least 70 genera. Sponges in the Makassar Strait showed significant differences based on individual abundance data. Pannikiang Island had the greatest abundance and diversity of sponges, and the lowest found in Gusung Toraja. The sponge composition of the three islands indicated that neighboring islands do not guarantee high similarity. Abstract Sponges are an important and dominant component of marine benthos which are threatened due to global environmental degradation. To establish appropriate conservation policies, the diversity and distribution of sponge must be understood. Meanwhile, the availability of sponge diversity and distribution especially in the Makassar Strait, is still lacking. This study aimed to investigated the diversity and distribution of the sponges composition in coral reef ecosystems on three less-explored islands in the Makassar Strait (South and West Sulawesi provinces, Indonesia). Sponge assemblages were sampled at a depth of 5 m using Underwater Photo Transect method, with a total area of 15 m2 at each site. We recorded a total of 137 morphospecies of sponges (N = 3978 individuals), 59 of which were restricted to Barrang Caddi, 39 to Gusung Toraja, and 92 to Pannikiang. Only 12 species were shared among all islands. We found ten morphological types of sponge, with the dominant type in all islands was encrusting. Our results showed that Pannikiang island represents the highest diversity and abundance of sponges, which had the largest area compared to the other islands and is surrounded by mangrove forests. There was a significant difference in species composition between Pannikiang and other islands.